POSITIVE THINKING FOR HUMAN RESOURCES AND ITS ROLE IN REDUCING JOB FRUSTRATION AN ANALYTICAL STUDY OF THE OPINIONS OF A SAMPLE OF EMPLOYEES AT AL-FURAT AL-AWSAT TECHNICAL UNIVERSITY - A. Okab, Ammar (Journal of Advance Research in Business, Management and Accounting (ISSN: 2456-3544), 2023)
The current research aims to study the relationship and impact between positive thinking of human resources in its five dimensions (positive daily performance, positive self-evaluation, self-evaluation of others, positive future expectations, positive social performance) and job frustration in its four dimensions (aggressive job frustration, withdrawal, job rationalization, and fixation Career), where the research was applied to a sample of employees at Al-Furat Al-Awsat Technical University, which included (104) employees at different job levels. The data were collected by means of the questionnaire and analyzed by the program (SPSS v.23). The research has reached results confirming the existence of a statistically significant correlation and impact between positive thinking of human resources and job frustration, and that positive thinking of human resources contributes to promoting better relations with co-workers and encourages more positive interactions, and one of the most important conclusions reached by the research where The senior management at Al-Furat Al-Awsat Technical University should adopt a special philosophy in positive thinking of human resources based on the adoption of functional features of positive thinking of the human resource in a reflective manner and purposeful and logical awareness so that employees are able to control their actions towards indicators of job frustration.